PEMBELAJARAN BERBASIS KEBUDAYAAN LOKAL DI LEMBAGA TK SEKAR SARI DI KECAMATAN PULOMERAK - Flavia Salsabila, Azqia; Kusumawardani, Ratih; Khosiah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of social development in early childhood, particularly in play involvement and the ability to build relationships with teachers and peers. The issue raised is that there are still children who are less active in play activities and have not yet optimally developed social interactions in the school environment. The purpose of this study is to identify efforts that can be made to increase children's involvement in play and their ability to build social relationships. The research methodology used is a qualitative approach with descriptive research type. The research subjects are early childhood children in group B (5–6 years old). Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was conducted descriptively by organizing the data, grouping it, and drawing conclusions from the findings obtained. Research results show that the implementation of structured play activities, appropriate stimulation, and the active role of teachers in guiding and facilitating social interactions can increase children's engagement in play. In addition, children also show improvements in their ability to interact, cooperate, and build positive relationships with teachers and peers. Thus, proper learning strategies can optimally support children's social development.